Views of social work students on the use of social media network - Khoza, Nokulunga (My University, 2016)
The use of social networks amongst students has increased drastically in recent times. Students use social networks such as Facebook within and outside of the university grounds. There are various reasons as to why students use social networks: firstly students use social networks to keep up with the latest trends on social media, secondly students use social media to keep in contact with family and friends, lastly students may use social networks to attain information which is relevant to their daily lives as both students, citizens of South Africa and the world. According to Bridgestock (2013) students have had challenges due to the use of social media however they have also benefited from the use of social media. Social workers are guided by the code of ethics in which they need to abide with in order to practice their work with clients. The research sought to understand how social work students view the use of social media networks. The main focus of the study was to find out how social work students incorporate their ethics and values into the use of social media networks. The study was located within a qualitative research paradigm and purposive sampling was used. The sample consisted of (10) ten third year social work students, a semi-structured interview schedule was used as part of the tool of the study. To collect data the researcher had one on one interviews with the participants. Thematic analysis was used as a method to analyse data during the interviews. The main findings of the study were that social work students mostly use WhatsApp and Facebook as a preferred method of communication on social media networks. Other findings noted that social work students have had good and bad experiences on social media. Good experiences were that students were able to remain updated with what is happening around the world, bad experiences included students being stalked or attacked. Furthermore the study revealed the behaviour social work students portray on social media networks. Students post inspiring quotes on social media however there are those students who post nude pictures. It was found ethics and values are not incorporated much with the use of social media networks. It was recommended that the code of ethics relooks at the values and ethics so that they will be able to accommodate everybody and they should focus on the importance of using social media and incorporating the ethics and values. Key words: Views, social work, students, social media.
The Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand In partial fulfilment of the requirements For the degree Bachelor of Social Work